Effects of seasonal, ontogenetic, and genetic factors on lifespan of male and female progeny of Arvicola amphibius - Nazarova, Galina (Frontiers in Genetics, 2013)
The water vole (Arvicola amphibius) in the forest-steppe of West Siberia is known to have wide fluctuations in abundance. These fluctuations are accompanied by changes in birth and death rates, sex-age structure of the population, and individual morphophysiological and behavioral characteristics of the animals. Survival of the animals depends on season, phase of population cycle, and sex. Based on the data of long-term captive breeding of water voles, the maximal lifespan of males was found to be 1188 days and that of females, 1108 days. There were no differences between the sexes in mean lifespan. The probability of living 2 years or longer was 0.21. Individuals who began breeding at an older age had a significantly longer lifespan and produced more offspring. The survival curves of the spring-born animals were steeper than of those summer/autumn-born. Maternal factors had differential effect on males and females with respect to lifespan. Male lifespan correlated negatively with maternal age, parity, and litter size, whereas female lifespan did not correlate with these characteristics. To estimate heritability, parent-offspring correlations of a lifespan were calculated, as well as full-sib intraclass correlations. No statistically significant correlation was found between sons’ and maternal, sons’ and paternal, and daughters’ and paternal lifespans. Daughters’ lifespan correlated positively with maternal lifespan (r = 0.21, p < 0.001). Female full-sibs and male full-sibs had the same intraclass correlations, 0.22, p < 0.001. The differences between heritability estimates obtained by different methods may be explained by sex-specific genetic controls over lifespan and/or sex-specific effects of the environment.